2021
DOI: 10.1155/2021/8821073
|View full text |Cite
|
Sign up to set email alerts
|

Use of Laser in Sleep Disorders: A Review on Low Laser Uvulopalatoplasty

Abstract: Study Objective. The objective of this study is to find the effectiveness of the low laser therapy on uvulopalatoplasty/soft palate in sleep apnea patients and snoring. Also, this study aims to touch base on the effectiveness of the Er:YAG and combined use of Er:YAG and Nd:YAG lasers for the uvulopalatoplasty. Methods. A comprehensive and systematic literature review was conducted using PubMed, Google Scholar, Cochrane Central Register of Controlled Trials, Embase, Web of Science, the US National Institutes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The panel reviewed 2 meta-analyses 112,113 and several studies addressing NALT in treating adult OSA or snoring. [114][115][116][117][118][119][120][121][122][123][124] The majority of the studies used Er:YAG 2940-nm laser stimulation.…”
Section: Adult Osamentioning
confidence: 99%
See 1 more Smart Citation
“…The panel reviewed 2 meta-analyses 112,113 and several studies addressing NALT in treating adult OSA or snoring. [114][115][116][117][118][119][120][121][122][123][124] The majority of the studies used Er:YAG 2940-nm laser stimulation.…”
Section: Adult Osamentioning
confidence: 99%
“…[114][115][116][117][118][119][120][121][122][123][124] The majority of the studies used Er:YAG 2940-nm laser stimulation. The successful outcomes reported in one of the review articles 113 confounded ablative and nonablative studies as well as animal studies and, therefore, overstated the limited evidence to support NALT. The limitations to the studies included lack of control groups and control group dropout data.…”
Section: Adult Osamentioning
confidence: 99%
“…As early as 2011, dentists were using erbiumdoped yttrium aluminium garnet lasers (Er:YAG) in a nonsurgical manner to decrease snoring to improve patient quality of life. 4 The use of nonsurgical lasers for treating snoring has become very popular, with two lasers dominating the market: the Lightwalker AT-S by Fotona (specific protocol for snoring: Nightlase) and the Solea by Convergent (specific laser protocol for snoring: Solea Sleep). 5,6 However, as of 2020, research still showed that although nonsurgical laser therapy was able to significantly decrease snoring, it is not an effective treatment for OSA.…”
Section: Introductionmentioning
confidence: 99%